Comparing shades of darkness: trolling victims’ experiences on social media vs. online gaming - Cook, Christine L.; Tang, Simon Y.-C.; Lin, Jih-Hsuan Tammy (Frontiers in Psychology, 2023)
Although there is ample literature available on toxicity in games, as there is regarding trolling on social media, there are few to no cross-platform studies on toxicity and trolling. In other words, the extant literature focuses on one platform at a time instead of comparing and contrasting them. The present work aims to rectify this gap by analyzing interviews from a larger study of 22 self-proclaimed victims of in-game trolling to not only determine whether social media or gaming communities are considered more toxic but also to explore how definitions of the word ‘trolling’ change depending on the platform in question. We found that while definitions of in-game trolling behavior focused on behavioral styles of trolling (e.g., throwing one’s avatar into enemy fire to disadvantage one’s team, and blocking other players’ avatars’ movement), social media trolling is defined by more sinister actions such as misinformation spreading and ‘canceling’ other users. We also found that gaming is perceived as generally more toxic than social media, often due to company policies or lack thereof. Practical and theoretical implications for the study of toxicity in all online communities – gaming or social-media based – are discussed.